Administration of hATSCs results in recovery of cerebral infarction animal model - Lee, Tae Hoon (Journal of Medical Care Research and Review, 2020)
To examine pathway of stem cell transplanted to the brain, stem cells were infected with flourescence. hATSCs in the infarct region were mostly located at the border between intact brain tissue and the area of the infarction and in other sections within the infarct cavity. Examination of section with flourescence indicated that there was significant gliosis or infiltration of leukocytes around the implantation site of the stem cell. Implanted stem cell integrated and migrated to multiple areas of the brain including the contrallateral cortex. The cells persisted in the sites to which they migrated at 30 days after implantation. The heaviest concentrations of cells were transplanted into rats at 24hr after MCAO, more cells were migrated into injured area of brain cortex. Stem cell in the infarct region were found at the border between intact brain tissue and the area of infarction and within the infarct cavity.